Enhancing patient participation in discharge medication communication: a feasibility pilot trial - Elizabeth Manias; Andrea P Marshall; Wendy Chaboyer; Georgia Tobiano; Trudy Teasdale; Sharon L Latimer; Kellie Wren; Kim Jenkinson (BMJ Open, 2024)
Objectives To pilot test a co-designed intervention that enhances patient participation in hospital discharge medication communication.Design Pilot randomised controlled trial.Setting One tertiary hospital.Participants Patients who were ≥45 years of age; ≥1 chronic illness and ≥1 regularly prescribed medication that they manage at home were recruited between October 2022 and May 2023. Healthcare professionals on participating units completed surveys.Intervention The co-designed intervention included three websites: a medication search engine, a medication question builder and tools to facilitate medication management at home. Inpatient posters contained QR codes to provide access to these websites.Primary and secondary outcome measures The primary outcomes were the feasibility of study processes and intervention acceptability. Feasibility of study processes was measured in terms of recruitment, fidelity, retention, missing data and contamination. Patients in the intervention group and healthcare professionals on the wards self-reported intervention acceptability. Secondary outcomes were medication understanding, use, self-efficacy and healthcare utilisation.Results 60 patients were recruited and randomised; half in each study group. The intervention was largely delivered as intended, and 99.7% of data collected was complete. In total, 16/59 (27.1%) patients were lost to follow-up 28 days after hospital discharge, and 3 patients in the usual care group reported that they saw the intervention poster prior to hospital discharge. 21 of 24 intervention group patients (87.5%) deemed the intervention acceptable, while half of the healthcare professionals (n=5, 50%) thought it was acceptable.Conclusions We demonstrated that in a future definitive trial, intervention fidelity would be high with little missing data, and patients would likely find the intervention acceptable. Thus, a larger trial may be warranted, as the intervention is implementable and approved by patients. However, additional strategies to increase recruitment and retention of eligible participants are needed. Healthcare professionals may require more preparation for the intervention to enhance their perceptions of intervention acceptability.Trial registration number ACTRN12622001028796.